Case report: 11 years on hemodialysis with a 4-year-old baby girl: A success story - Mambap, Alex Tatang; Bechem, Efuetnkeng; Kan, Kate Mafor; Laah, Sylvain Njoyo; Sunjoh, Frida; Ashuntantang, Gloria Enow (Frontiers in Medicine, 2023)
Despite advances in clinical management and dialysis care, the outcome of unplanned pregnancy in women on maintenance hemodialysis (MHD) remains a difficult journey for the patient, fetus, and healthcare staff, particularly in low-resource countries. We report the successful outcome of a pregnancy in an anuric woman on twice-weekly maintenance hemodialysis for chronic glomerulonephritis since November 2012 in Cameroon. She was discovered pregnant at 18 weeks of gestation. The pregnancy was maintained until 36 weeks when a healthy 2,270 g female baby was delivered by elective cesarean section for tight nuchal cords and intrauterine growth retardation. The mother’s post-partum period was uneventful. Except for hypoglycemia shortly after birth, the baby was fine. The patient is still on hemodialysis after 4 years, and the child is healthy and attending school.